Exploring Difference or Just Watching the Experts at Work? Interrogating Patient and Public Involvement (PPI) in a Cancer Research Setting Using the Work of Jurgen Habermas. (December 2018) - Bissell, Paul; Thompson, Jill; Gibson, Barry
Patient and public involvement (PPI) has emerged as a key consideration for organisations delivering health research and has spawned a burgeoning literature in the health and social sciences. The literature makes clear that PPI in health research encompasses a heterogeneous set of practices with levels of participation and involvement ranging from relatively minimal contributions to research processes to actively driving the research agenda. In this article, we draw on the work of Jurgen Habermas to explore the ways in which PPI was accomplished in a cancer research setting in England. Drawing on ethnographic data with PPI participants and professional researchers, we describe the ways in which the life-world experiences of PPI participants were shaped by the health research system. We argue that PPI in this setting is less about exploring differences with regard to a plurality of expertise and more about simply watching or supporting the professional researchers at work.